Perancangan Website Pembelajaran Bahasa Jepang dengan Fokus Materi Klausa melalui Metode Waterfall - Dimas Ardiansyah; Ade Irma Purnamasari (LPPM STT Terpadu Nurul Fikri, 2024)
Interest in Japanese is increasing in Indonesia, especially at LPK IHMI Cirebon, along with the growth of bilateral relations and information technology. This research aims to improve Japanese language learning, especially Japanese clause material through website design at LPK IHMI Cirebon. Conventional methods that are less interactive become obstacles to active participation of students. An innovative approach is proposed by utilizing a website, especially through the WordPress platform, and referring to the book